Pengaruh Kepercayaan Publik Terhadap Partisipasi Masyarakat Dalam Musrenbang Kelurahan Krendang Kecamatan Tambora Kota Administrasi Jakarta Barat - Aulia Sholihah; Tulus Santoso (Jurnal Ilmu Administrasi Publik, 2022)
This thesis discusses the effect of public trust on community participation in the Development Planning Deliberation of Kelurahan Krendang, Tambora District, West Jakarta Administrative City. The background of this research is the lack of public trust in the government, the lack of supporting facilities and infrastructure, and the lack of interaction between the government and the community. The purpose of this study was to determine the influence of public trust on community participation in the Development Planning Deliberation of Kelurahan Krendang, Tambora District, West Jakarta Administration. The method used in this study is a quantitative method through the distribution of questionnaires, with a population of 23,433 residents and a sample of 100 respondents who were selected using saturated sampling technique. The results of data analysis with the help of SPSS version 23 for Windows show that based on the results of the t test, it is known that the public trust variable has a positive and significant effect of 0.827 or 82.7% on the variable of community participation in the Development Planning Deliberation, with a t-value greater than t-table. The remaining 17.3% is the influence of other factors not examined in this study